The Incorporation of a Spiritual Emergency Experience Into a Client's Worldview: A Grounded Theory. (November 2019) - Sedláková, Hana; Řiháček, Tomáš
This study is focused on the process of constructing the meaning of a spiritual emergency experience. In the context of this study, spiritual emergency is understood as an experience of psychotic nature, defined by criteria such as good preepisode functioning, nonordinary states of consciousness, awareness of the intrapsychic nature of the process, or preserved ability to cooperate. In-depth interviews with 13 participants who experienced an episode of spiritual emergency were analyzed using the grounded theory method. The analysis yielded a core category titled "The incorporation of a spiritual emergency experience into a client's worldview." The process of incorporation was conceptualized by two complementary paths: (a) a Suppressive path characterized by an effort to mitigate or eliminate symptoms, considering them as a personally meaningless pathology, and return to a previous state of functioning and (b) a Facilitative path characterized by an acceptance of symptoms, a search for their meaning, and eventually, the adoption of a new perspective. The results are discussed in relation to different theoretical approaches to psychotic experiences.